Implementation of Individual Counseling of Cognitive Dispute Techniques to Improve the Psychological Welfare of Junior High School Students - Luluk Ermawati; Imaratul Ulwiyah; Ade Irma Noviyanti (Jurnal Kiprah Pendidikan, 2025)
This study aims to implement and evaluate the effectiveness of individual counseling with cognitive dispute techniques in improving the psychological well-being of grade VII students at SMP IT Grafika Pesanggaran. The background of this study is based on the importance of psychological well-being in early adolescence, especially in dealing with academic, social, and emotional pressures in the school environment. The research method used is quantitative experimental with a single subject research (SSR) approach and A-B design, consisting of a baseline phase (A) and an intervention phase (B). The research subjects were selected purposively, namely grade VII students who had a low level of psychological well-being based on the results of initial measurements. The intervention was given in the form of individual counseling using cognitive dispute techniques, which is the process of helping students recognize and dispute irrational or negative thoughts that hinder their well-being. During the counseling process, repeated measurements were taken to see any changes in the psychological condition of students before and after the intervention. The results of this study are expected to show an increase in aspects of students' psychological well-being after being given intervention, such as increased self-confidence, self-control, meaning of life, and positive relationships with others. In addition, this study also provides a practical overview of the application of cognitive counseling techniques in the context of education and guidance in schools. This research not only contributes to the field of guidance and counseling, but also becomes a reference for BK teachers and education practitioners in developing counseling services based on cognitive approaches to support students' mental health as a whole..